2020
DOI: 10.1002/ddr.21773
|View full text |Cite
|
Sign up to set email alerts
|

Hirudin prevents vascular endothelial cell apoptosis and permeability enhancement induced by the serum from rat with chronic renal failure through inhibiting RhoA/ROCK signaling pathway

Abstract: Endothelial cells injury and activation contribute to arteriovenous fistula (AVF) stenosis.Hirudin (Hiru) can inhibit the activity of thrombin, which was reported to enhance endothelial cell permeability and promote vascular inflammatory responses. RhoA/ROCK signaling pathway is also important in regulating vascular endothelial permeability. This study aimed to investigate the role of Hiru on the viability and permeability of human umbilical vein endothelial cells (HUVECs) following stimulation of serum from r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Animal experiments were performed as previously described ( 23 ). A total of 40 male Wistar rats (age, 6-7 weeks; weight, 160-180 g) were obtained from Nanjing Jiancheng Bioengineering Institute, and maintained in a 12 h light/dark cycle, with 50-60% humidity at 22-26˚C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal experiments were performed as previously described ( 23 ). A total of 40 male Wistar rats (age, 6-7 weeks; weight, 160-180 g) were obtained from Nanjing Jiancheng Bioengineering Institute, and maintained in a 12 h light/dark cycle, with 50-60% humidity at 22-26˚C.…”
Section: Methodsmentioning
confidence: 99%
“…All experiments were performed as previously described ( 23-26 ). Blood samples were centrifuged at 1,000 x g for 10 min to collect serum.…”
Section: Methodsmentioning
confidence: 99%
“…Hirudin is a promising anticoagulant drug, a large number of studies have indicated that hirudin has the functions of inhibiting platelet aggregation, reducing blood lipids, regressing atherosclerosis, promoting the absorption of cerebral hematoma, and relieving intracranial pressure ( Azzopardi et al, 2011 ; Bian et al, 2020 ; Junren et al, 2021 ; Nilius et al, 2021 ). In the treatment of cardiovascular diseases, the roles of hirudin in reducing inflammatory infiltration of vascular tissue, inhibiting the proliferation of vascular smooth muscle cells, improving endothelial dysfunction, regulating autophagy levels, resisting oxidative damage, and accelerating lipid metabolism have been gradually revealed ( Dong et al, 2016 ; Yu et al, 2018 ; Wang et al, 2019 ; Zhang H. et al, 2020 ; Chen et al, 2021 ). However, the mechanism by which hirudin improves myocardial hypertrophy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, accelerated programmed cell death or apoptosis has been demonstrated among patients with chronic renal failure (CRF) which may be caused by uremic toxins ( Chen et al, 2021 ). An increased Fas ligand (FasL, a 40-kd type II integral membrane protein) level in ESRD patients has been reported which is a key regulatory apoptotic pathway of the cell death ( Perianayagam et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%